Reproductive technology in domestic carnivorous - Lopes, Maria Denise [UNESP] (My University, 2010)
Background: The delay in development of artificial reproduction techniques on carnivorous could be due to countless reasons, but the lack of commercial interest is probably the most important one. The majority of canines are small structures, canidae are extremely fertile and a great number of species are adapted to domestication or captivity. Finally, the canine gamete physiology presents a difficult adaptation of technology knowledge obtained from other species. Furthermore, domestic felines are animals of company and there is no interest in reproducing them in a large scale, as it has been observed in other domestic animals, however, besides of being a valuable model for the development of in vitro techniques, the domestic cat is also used as an embryo receptor for different species of small wild felines due to physiological similarities among them, in vitro embrionary development, Review: It was reviewed the main insights about the reproductive physiology in female dogs, in vitro oocytary maturation (IVM), pregnancy and conception rate with dogs' frozen/unfrozen semen and PIV in domestic cats. The majority of mammal oocytes restart meiosis spontaneously after ovulation and reaches MII in artificial environment; in an in vitro maturation system in bovines, around 90% of oocytes complete their maturation, although its development capacity can be reduced subsequently. The success of IVM in canidae have been limited, with maturation rate varying from 0 to 58%, usually around 20%. The greatest difficulties include oocyte quality, hormonal environment, protein supplementation, cumulus / oocyte cell interaction, donor breed and age, culture systems, oxygen tension, amino acids, growth factor and sequential means. The freezing process reduces the quality of the semen, firstly because it reduces the number of living sperms and secondly because freezing produces cell modifications that could alter the sperm motility, longevity, integrity of membranes and its fertilizing capacity. Conclusion: Nowadays, several researches are being performed with the aim of increasing viability after dogs' and cats' semen is unfrozen, using extenders, cryoprotectors, freezing and unfreezing curves, addition of antioxidant substances. The aim of this text is to inform about the improvements obtained on the artificial reproduction techniques, emphasizing the oocytary maturation in female dogs, semen cryopreservation and artificial insemination in domestic dogs and cats.
Keywords: Artificial insemination; Dog and cat; Oocytary maturation; Semen cryopreservation; Animalia; Canidae; Canis familiaris; Felis catus; Mammalia